Competition stress leads to a blunting of the cortisol awakening response in elite rowers - MacDonald, D.; Wetherell, M. A. (Frontiers in Psychology, 2019)
Background: Anticipation of forthcoming demands is often met with biological up-regulation, for example, levels of the stress hormone cortisol are typically elevated immediately prior to an anticipated event. Similarly, the cortisol awakening response (CAR), a surge in cortisol in the period following waking, is elevated on days of anticipated demand and this is viewed as an adaptive response in the preparation for challenge. This study assessed the effects of competition as an anticipated challenge in elite rowers.